Financial Distress Analysis of Top 100 Malaysian Public Listed Companies during COVID-19 Pandemic using Altman Z-Score Analysis - Hashim, Marshita; Muhammad, Kamaruzzaman; Ghani, Erlana K.; Abd Azis, Maz Ainy (International Journal of Economics and Financial Issues, 2024)
The outbreaks of the COVID-19 pandemic at the beginning of 2020 have led to considerable economic pressure worldwide, including in Malaysia. The Malaysian government has issued a series of Movement Control Orders (MCOs) requiring companies in most sectors to be closed to the public, with the exception of essential services and certain sectors. The objective of this study is to analyse whether there is a difference in the financial distress of Malaysian companies before and during the COVID-19 pandemic by using the Altman Z-score method. In this study, the annual reports of 83 different companies from 2017 to 2019 and the post-pandemic period (2020 to 2021) were analysed. This study shows that the global COVID-19 pandemic scenario has a significant impact on the logistics and transport sectors, the consumer goods market, and the manufacturing sector. A significant number of companies have been shaken and are now struggling with difficult circumstances as a direct result of the COVID-19 outbreak. This study also shows that almost half of the companies face the possibility of going bankrupt within this period. Surprisingly, there are companies that seem to have improved their performance despite the widespread COVID-19 epidemic. The findings of this study can provide valuable insights for regulators looking to develop strategies to help listed companies cope with future pandemic-related problems.